2005
DOI: 10.1080/13504850500044104
|View full text |Cite
|
Sign up to set email alerts
|

Proposed modified probit model incorporating non-parametric density estimation: how to measure asymmetric information in the health insurance market?

Abstract: On the basis of the theory of Chiappori and Salanie (2000), this paper proposes a simple modified bivariate Probit model incorporating non-parametric kernel density estimation. The model is applied to test asymmetric information in a health insurance market, using MEPS96 data.1 Results show that asymmetric information (whether moral hazard or adverse selection) exists between the contract of insurance coverage, and some non-emergency visits services, which appear to support the conclusions of Cardon and Hendel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The study further recommended a shift in focus from information sharing to interpretation schemes sharing. Aoki (2005) carried out a study in UK and sought to know how to measure asymmetric information in the health insurance market by identifying the ways of measuring information asymmetry. The study used a simple modified bivariate Probit model incorporating non-parametric kernel density estimation to test asymmetric information in a health insurance market.…”
Section: Empirical Literaturementioning
confidence: 99%
“…The study further recommended a shift in focus from information sharing to interpretation schemes sharing. Aoki (2005) carried out a study in UK and sought to know how to measure asymmetric information in the health insurance market by identifying the ways of measuring information asymmetry. The study used a simple modified bivariate Probit model incorporating non-parametric kernel density estimation to test asymmetric information in a health insurance market.…”
Section: Empirical Literaturementioning
confidence: 99%
“…This class of models embodies the normality assumption for the conditional probability of the binary dependent variable given observables. Aoki [1] followed a similar testing strategy but considered non-parametric estimation procedures. The study was based on the Medical Expenditure Panel Survey data in 1996 and found some evidence for asymmetric information.…”
Section: Occupational Variablesmentioning
confidence: 99%
“…1 Results for adverse selection are scant and found only in some of the papers that analyze specific segments of the markets. Within the second group, the evidence on adverse selection was mixed.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation